Local Languages, Global Futures : Language, Learning, and Sustainability in Africa (Akademische Verlagsgemeinschaft München AVM, 2026)
This volume explores the central role of African languages in shaping inclusive and sustainable futures across the continent. While Africa has long been viewed primarily as a source of extractable resources, its future strength lies in its people. With higher education access below 10% in Sub-Saharan Africa—compared to nearly 80% in the Global North—there is both an urgent need and a major opportunity to expand learning. Such expansion will only succeed if students can study in languages they know; using African languages as mediums of instruction is essential to unlocking the continent’s human potential. Drawing on perspectives from education, technology, public communication, and indigenous knowledge, the contributions show how local languages function as cultural anchors and as drivers of learning, innovation, and social transformation. They address issues such as scientific communication in African languages, terminology development, multilingual education policies, digitization and digital divides, language visibility in public life, education for hunter-gatherer communities, and media and the arts, illustrated through cases from across the continent. A concluding theoretical chapter examines broader challenges and opportunities for multilingual education in Africa. Together, the chapters demonstrate that strengthening African linguistic resources is vital for decolonizing knowledge production, empowering communities, and reimagining education systems that reflect Africa’s diverse realities and aspirations. With contributions from Doris Löhr, Comfort Beyang Oben Ojongnkpot, Taiwo Oloruntoba-Oju, Bert van Pinxteren, Ayodele Yusuff, Feyi Ademola-Adeoye, Adédoyinsolá Omowùnmí Eleshin, Emilisco Jones Enoachuo, Sarita Monjane Henriksen, Tomoe Noguchi, Omusula W. Omuholo
Keywords: African languages; Multilingual education in Africa; Language as medium of instruction; Decolonization of knowledge; Indigenous knowledge and education; Language policy and planning; Higher education in Sub-Saharan Africa; Inclusive and sustainable development; Linguistic diversity and social transformation; Language; technology; and digitization